PENGEMBANGAN LITERASI KREASI (KREATIF DAN KONTRIBUSI): UPAYA PENINGKATAN CINTA LITERASI PADA SISWA SD NEGERI 060915. KEC. MEDAN SUNGGAL: - - Thresia Yohana Sembiring; Nurhayati Nurhayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to explore and evaluate efforts made to increase literacy love among primary school students. Literacy plays a crucial role in students' intellectual and social development, and understanding and appreciation of literacy can enrich their educational experience. The research method involved qualitative data collection through classroom observation, interviews with teachers and students, and analysis of documents related to the literacy programme that had been implemented. The results showed that efforts to increase a love of literacy involved innovative teaching strategies and the integration of literacy into the curriculum. Teachers actively promote students' interest in reading through activities such as book discussion groups, storytelling and storytelling performances, visits to the library, promoting literacy corner projects in classrooms, and enlivening the walls and corridors of the school with students' literary works. In addition, science literacy programs can also enhance students' knowledge of nature, and teacher storytelling programs can improve both teachers' and students' appreciation of literature. These findings can provide insights for other schools that want to increase a love of literacy at the primary level, emphasising the importance of collaboration between teachers, students, and parents in creating an educational environment that supports children's literacy development